Edukasi Kesehatan tentang Menu Seimbang pada Ibu Balita di Desa Lembar Selatan - Aryani, Ni Putu; Afrida, Baiq Ricca; Idyawati, Susilia; Jannatih, Sri Hawari (Jurnal Abdimas Kesehatan (JAK), 2025)
Stunting is a critical menu problem related to the growth and development of toddlers. Stunting is a menu problem that continues to occur due to insufficient food intake over a long period of time and inappropriate or unbalanced food intake with the child's menu needs. The purpose of this community service is to provide information on providing a balanced menu to mothers who have toddlers through health education. This activity will be carried out in Lembar Selatan Village, Lembar District, West Lombok Regency in July 2024. The target of this activity is 30 mothers who have toddlers. The expected results of this community service activity are increased cognitive, affective and psychomotor skills about providing a balanced menu to mothers who have toddlers. The methods used are health education and discussion. Before the community service activity is carried out, of course, a licensing process will be carried out with the local government first. Coordination is carried out with the village head to invite participants and determine the location of the activity. The next preparation is the creation of leaflets, materials and guidebooks.